The application of performance management practices in Chinese school A case study of School X - Luo, Min (2018)
The school effectiveness and educational quality are given more attention in recent years, since the increased investment in education and the increased demand for accountability by society. Therefore, the performance management practices in schools has become a public topic. The performance of Chinese students in science, reading and mathematics has ranked tenth in the Programme for International Student Assessment in 2015. While the student representatives who took the test come for Beijing, Shanghai, Jiangsu and Guangdong. Those are well-developed cities in China. However, in fact, the poor development of basic education can be seen in rural areas. It is necessary to develop educational quality in rural areas and maintain high education quality in urban areas. In this case, performance management practices and self-evaluation can contribute to develop the education quality. In this paper, the background of performance management will be introduced in the beginning. Next, through reviewing the related literature, which provides a theoretical methodology and analytical framework to analyse the case study. After analysing the case, a better understanding of performance management practices can be gained. Based on the results of the study, some suggestions can be provided to structure a developed performance management process in Chinese school.